Effect of yoga on mental health and emotional maturity of visually challenged students - SAVITA GAHLAWAT (Dr. Chinmay Pandya, 2013)
The study was designed to examine whether practice of Yoga has a positive effect on the mental health and emotional maturity of visually challenged students. The sample consisted of 20 visually challenged students drawn purposively from a Govt. School for the Blind. The main objective of the study was to see the effect of yoga on mental health and emotional maturity of visually challenged students. A Yoga training programme was designed and the subjects were exposed to it for a period of four weeks. The effects of yoga on mental health of visually challenged students were measured by administering Singh & Gupta's Mental Health battery whereas effects on emotional maturity were obtained by applying Singh and Bhargava's Emotional Maturity Scale. The data was analyzed in terms of mean, S.D and t-test. The results indicate that on the whole the level of mental health and emotional maturity of visually challenged students improves after the practice of yoga. Significance differences were found between mean gain scores on all the dimensions of Mental health Battery and Emotional Maturity Scale. Hence, it can be concluded that yoga puts a positive effect on the mental health and emotional maturity of the practitioners. The study has its implications for school administrators, policy makers, parents, teachers, community leaders, and rehabilitation workers.